Linguistic-Semantic Investigation of the Disease "Deafness" in the Uzbek, Russian and English Languages - Abdurakhmanova Madina (Peerian Journals Publishing, 2022)
Mankind has emerged that people are interested in improving the health of themselves and their loved ones, prolonging their lives, and for this they have spared both material and spiritual resources. Because only a healthy person can feel the full pleasure of life. That is why medical vocabulary has been and continues to be actively used not only by representatives of the medical field, but also among ordinary people. These phenomena have not escaped the notice of linguists and have always attracted them. Work on many studies in medical terminology has not yet stopped. In this article, we want to investigate the use of the term deafness in the figurative meaning and briefly describe the symptoms of the disease. Thus, we planned to determine lexical-semantic features of the term in the Uzbek, Russian, and English languages, whether there is a similarity to the disease condition when the term deafness is used in the figurative sense.
Keywords: deafness; figurative meaning; derivative; karlik; глухота